Pengaruh Personal branding Abidzar Al-Ghifari Terhadap Purchase intention Melalui Brand image Pada Film Remake “A Business Proposal" - Fitri Hikmah Sufiah; Dita Purwita; Nofriska Krissanya (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to determine whether there is a positive and significant influence of Abidzar Al-Ghifari's Personal branding on Purchase intention thru Brand image in the remake film A Business Proposal. This type of research is quantitative research with a survey approach. The sampling technique used is the purposive sampling approach. Data collection was carried out using a questionnaire instrument on the Google Forms platform with a 6-point Likert scale, which was distributed online to 220 respondents. The criteria for the respondents were: individuals aged 17-35 years, residents of the Special Region of Jakarta, individuals who were aware of the remake film A Business Proposal, individuals who knew Abidzar Al-Ghifari as the main actor in the remake film A Business Proposal, and individuals who were active on social media. This data analysis was conducted using inner models testing, outer models testing, and hypothesis testing with the assistance of SEM-PLS software. The results of the study indicate that Personal branding has a positive and significant influence on Brand image. Personal branding has a positive and significant influence on Purchase intention. Brand image has a positive and significant influence on Purchase intention. Additionally, Personal branding has a positive and significant influence on Purchase intention thru Brand image. The findings of this study provide important insights for marketing strategies, particularly in the effective use of Personal branding to create a positive and strong Brand image and increase public Purchase intention in the Indonesian film industry.